Advances of Commercial and Biological Materials for Electron Transport Layers in Biological Applications - Yin, Zhifu; Lu, Biao; Chen, Yanbo; Guo, Caixia (Frontiers in Bioengineering and Biotechnology, 2022)
Electron transport layer (ETL), one of the important layers for high-performing perovskite solar cells (PSCs), also has great potential in bioengineering applications. It could be used for biological sensors, biological imaging, and biomedical treatments with high resolution or efficiency. Seldom research focused on the development of biological material for ETL and their application in biological uses. This review will introduce commercial and biological materials used in ETL to help readers understand the working mechanism of ETL. And the ways to prepare ETL at low temperature will also be introduced to improve the performance of ETL. Then this review summarizes the latest research on material doping, material modification, and bilayer ETL structures to improve the electronic transmission capacity of ETLs. Finally, the application of ETLs in bioengineering will be also shown to demonstrate the ETLs and their used material have high potential for biological applications.